An obscured narrative in the political economy of colonial commerce in Lesotho, 1870-1966 (Historia, 2021)
This paper examines the political economy of colonial commerce in Lesotho - then Basutoland. It argues that although pivotal and appropriate, the political economy narrative alone is limited as an explanation for other dynamics which shaped Lesotho's colonial commerce. It provides a radically simplified bi-polar picture in which European and Indian traders (the more powerful actors) on the one hand, and Basotho traders (the weaker actors) on the other, participated in antagonistic silos. Using historical records and the political economy of Lesotho as a context, this article identifies the existence of a dialectical and multifaceted relationship between these two categories. This was manifested in the interdependent and indispensable relationship between everyday economic pragmatism and collective political activism. This is an under-played catalyst that contributed to the shaping of the country's business landscape in the colonial period.  Hierdie artikel ondersoek die politieke ekonomie van koloniale handel in Lesotho (toe Basoetoland genoem). Daar word geargumenteer dat die politiek-ekonomiese narratief, hoewel deurslaggewend en geskik, as sodanig beperk is as 'n verklaring vir ander dinamiese verskynsels wat Lesotho se koloniale handel bepaal het. Dit skets 'n radikaal vereenvoudigde bipolêre prentjie waarin Europese en Indiese handelaars (sterker rolspelers) aan die een kant, en Basoeto-handelaars (swakker rolspelers) aan die ander kant, in antagonistiese silo's opgetree het. Deur van historiese rekords gebruik te maak, en met politieke ekonomie as 'n konteks, identifiseer die referaat die bestaan van 'n dialektiese en veelvlakkige verhouding tussen hierdie twee kategorieë. Dit het gemanifesteer in die onderling afhanklike en onontbeerlike verhouding tussen individue se daaglikse ekonomiese pragmatisme en kollektiewe politieke aktivisme. Dit is 'n onderbeklemtoonde katalisator wat daartoe bygedra het om die land se sakelandskap in die koloniale tydperk te bepaal.
Keywords: Political economy approach; Colonial commerce; Politiek-ekonomiese benadering; Lesotho; Monopolie